Zfhx4 regulates endochondral ossification as the transcriptional platform of Osterix in mice - Eriko Nakamura (Nature Portfolio, 2021)
Nakamura et al. used expression studies to identify an enrichment of Zfhx4 in cartilage and revealed through global gene knock-down that it is required for proper endochondral ossification in mice. They further demonstrated a physical and genetic interaction between Zfhx4 and Osterix, which is of interest to the field of transcriptional regulation of mammalian endochondral ossification.